The complement of a subspace in a classical polar space - Petelczyc, Krzysztof (Ars mathematica contemporanea, 2019)
In a polar space, embeddable into a projective space, we fix a subspace, that is contained in some hyperplane. The complement of that subspace resembles a slit space or a semiaffine space. We prove that under some assumptions the ambient polar space can be recovered in this complement.
Keywords: complement; komplement; polar space; polarni prostor; projective space; projektivni prostor; prostor z režo; semiaffine space; semiafin prostor; slit space